Ethanol from photoperiod-sensitive sorghum: a study on biomass structure and process optimization - Xu, Feng (Kansas State University, 2013)
Cellulosic ethanol made from low cost lignocellulosic biomass has been considered as new generation transportation fuel with economic and environmental advantages. Photoperiod-sensitive (PS) sorghum, because of its high biomass yield (2.6 kg dry mass/m2), about 18% of soluble sugar in dry mass, and drought tolerance, is a promising biomass for ethanol production. The overall goals of this study are to develop an efficient approach to convert PS sorghum to ethanol and to understand the structural characteristics of biomass. For increasing the efficiency of biomass conversion, an integrated method, using diluted sulfuric acid pretreatment, has been developed to utilize both the structural polysaccharide (cellulose) and the soluble sugar (sucrose, glucose, and fructose) for fermentation. Response surface methodology was employed to optimize the pretreatment condition for maximizing the cellulose-glucose conversion. Simultaneous enzymatic hydrolysis and yeast fermentation was used for ethanol production. The effects of the buffer concentration, the inoculation dosage and time, and the fermentation temperature were investigated for maximizing ethanol yield. A total conversion efficiency of 77.2% and an ethanol concentration of 2.3% (v/v) were obtained after 72 h fermentation. About 210 kg (~266 Liters) ethanol could be produced from one ton dry mass of PS sorghum under the optimized condition. The structural features of the PS sorghum were studied using techniques including scanning electron microscopy and X-ray diffraction/scattering. Biomass at different botanic locations was investigated. Wide-angle X-ray diffraction (WAXD) study showed that the PS sorghum rind had oriented crystal peaks and the highest degree of crystallinity, whereas the crystalline structures of the inner pith and leaf were less ordered. The results from WAXD suggested that crystalline cellulose was melted at 120 °C before its significant degradation. Both the cellulose crystallinity and the crystal size at the dimension lateral to fiber direction increased as the temperature increased from 120 to 160 °C. The efficiency of enzymatic hydrolysis increased because the protective structure was damaged and most hemicellulose was removed, resulting in the increase in accessible area as suggested by small-angle X-ray scattering result of the increased length of microvoids. The results from WAXD also suggested a simultaneous hydrolysis and crystallization of cellulose by acid.
Keywords: Photoperiod-sensitive sorghum; Hydrolysis; Ethanol; Pretreatment; X-ray diffraction; Fermentation; Chemical Engineering (0542)